2006
DOI: 10.1213/01.ane.0000247965.41868.da
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Spinal Anesthesia on QT Interval in Preeclamptic Patients

Abstract: In this study, we measured the effects of spinal anesthesia on the corrected QT (QTc) interval in women with severe preeclampsia. Twenty-five preeclamptic (preeclamptic group) and 25 healthy pregnant women with normal arterial blood pressure and QTc interval (control group) were enrolled in this prospective, case-controlled study. Arterial blood pressure, heart rate, and QTc interval values were obtained before (baseline value) and at 5, 10, 20, 30, 60, and 120 min after initiation of spinal anesthesia. Total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
2
12
0
3
Order By: Relevance
“…44 In a study comparing preeclamptic patients (not LQTS parturients) with healthy controls, the QTc was prolonged prior to induction of spinal anesthesia in the preeclamptic group (452 ± 17.5 msec) but not in the control group (376 ± 21.4 msec). 45 When the spinal was administered the QTc normalized in the preeclamptic group and remained stable in the control group. 45 The authors suggested that the prolonged QTc at baseline was possibly secondary to hypocalcemia and hypertension, or to autonomic imbalance and sympathetic over activity.…”
Section: Regional Anesthesiamentioning
confidence: 95%
See 1 more Smart Citation
“…44 In a study comparing preeclamptic patients (not LQTS parturients) with healthy controls, the QTc was prolonged prior to induction of spinal anesthesia in the preeclamptic group (452 ± 17.5 msec) but not in the control group (376 ± 21.4 msec). 45 When the spinal was administered the QTc normalized in the preeclamptic group and remained stable in the control group. 45 The authors suggested that the prolonged QTc at baseline was possibly secondary to hypocalcemia and hypertension, or to autonomic imbalance and sympathetic over activity.…”
Section: Regional Anesthesiamentioning
confidence: 95%
“…45 When the spinal was administered the QTc normalized in the preeclamptic group and remained stable in the control group. 45 The authors suggested that the prolonged QTc at baseline was possibly secondary to hypocalcemia and hypertension, or to autonomic imbalance and sympathetic over activity. There are no studies investigating the effects of preeclampsia in LQTS, but one should be aware of the potential increase in the QTc.…”
Section: Regional Anesthesiamentioning
confidence: 95%
“…1,2 Alors qu'une étude réalisée par Sen et coll. a montré que l'intervalle QT était fréquemment allongé chez les pré-éclamptiques, 3 la survenue de ce type de complication pendant une anesthésie est peu connue. Nous rapportons un cas de torsades de pointes survenant lors d'une anesthésie générale pour césar-ienne dans un contexte de pré-éclampsie sévère.…”
Section: Au Rédacteur En Chefunclassified
“…La rachianesthésie permet d'éviter l'utilisation de ces agents; elle peut en outre contribuer, grâce au bloc sympathique, à la normalisation d'un QT prolongé chez la pré-éclamptique. 3 Conflit d'intérêt Aucun. …”
Section: Au Rédacteur En Chefunclassified
“…Se ha visto que la anestesia espinal también prolonga el QTc 92 , aunque el bloqueo adrenérgico y la analgesia que provee son deseables. Existen reportes de su uso exitoso en pacientes con LQTS en el campo de la obstetricia [93][94][95][96] . Algunos autores reportan la anestesia epidural como alternativa más segura, aludiendo al hecho de una instauración más gradual, con menor hipotensión, y por tanto, menos probabilidad de uso de drogas simpaticomiméticas 97 .…”
unclassified